Dr. Seuss's book of colors. - Seuss, Dr. (New York : A Bright and Early Book From Beginner Books, A Division of Random House, 2018)
Rhyming text and classic Dr. Seuss illustrations introduce young readers to colors
Ages 5-8.
Keywords: Colors -- Juvenile literature; Color; Readers